Natural Prenylated Xanthones as Potential Inhibitors of PI3k/Akt/mTOR Pathway in Triple Negative Breast Cancer Cells - Nguyen, Thi Thu Ha; Qu, Zhao; Nguyen, Van Tuyen; Nguyen, Thanh Tra; Le, Thi Tu Anh; Chen, Sibao; Ninh, Son The (Planta Medica, 2022)
Three prenylated xanthones, garcinone E (1), bannaxanthone D (2) and bannanxanthone E (3) were isolated from the leaves of Garcinia mckeaniana Graib. Their structures were elucidated by spectral methods and compared with literature data. To evaluate their anti-proliferative effects in tumor cells, firstly, cisplatin was used as a positive control and the effects of compound 1 – 3 were determined by performing MTT assay in MDA-MB-231, CNE-2 and A549 cancer cells. The results showed compound 1 – 3 exhibited stronger inhibitory effect than cisplatin in MDA-MB-231. Further effects of compound 1 – 3 in TNBC MDA-MB-231 and MDA-MB-468 cells were examined by performing cell cycle and apoptosis assays. The results indicated that compound 1 – 3 had ability to arrest cell cycle at G2/M phase and induce apoptosis. Furthermore, compound 2 significantly down-regulated PI3K, Akt and mTOR levels in both total proteins and phosphorylated form, which is its potential anti-cancer mechanism. These findings indicated that those prenylated xanthones might serve as promising leading compounds for the development of anticancer drug for TNBC.
Keywords: Garcinia mckeaniana Graib; Prenylated xanthones; Anti-proliferative effect; Triple-negative breast cancer; PI3k/Akt/mTOR pathway